PENGGUNAAN PUREE NENAS DAN PEPAYA PADA PEMBUATAN DODOL - Chasri Nurhayati; Rahmaniar Rahmaniar (Balai Riset dan Standardisasi Industri Palembang, 2010)
The objective of this research ae making dodol from admixture of fruits and knowng about formula of the dodol so can product the foods fulfill requiments. This research varies five (5) treatment and three(3) repetitions. First treatment is proportion between peneaple and papaya are treatment A4500g,750 g, treatment A3=700g,550g treatment A4=800g,450g and treatment A5=1000g, 250g. paramenter tested are water content ,protein content, ash content, couarse fiber and sugar content. The best treatment was gotton from treatment A4(additional of 800 g pinapple pure. Product characteristic produced are water content : 5,34%,ash content : 0,50%, couarse fiber : 0,33% and sugar content : 40,03%.